Hypervascularisation of colonic graft for oesophageal replacement: literature review and own experience - Varabei, Aliaksandr; Vizhynis, Yezhy; Makhmudov, Anvar; Chepik, Dzmitry; Arlouski, Yury; Gulevich, Margarita (Medical Studies/Studia Medyczne, 2017)
Colonic interposition in post-burn oesophageal strictures still remains a challenge. The main issue is the viability of the cervical portion of the colonic graft. The article provides a literature review on mesentericography and hypervascularisation of colonic graft for oesophageal replacement. The authors share their own experience. The study of the colic arterial anatomy enables one to choose its more perfused portion for oesophageal replacement. In insufficient blood supply, direct anastomoses with cervical or internal thoracic vessels have been proposed for hypervascularisation of the cervical part of graft. The technique of vessel ligation with a subsequent intensive collateral blood flow has been designed for hypervascularisation of the colonic graft.